Efffect of Enteromyxum leei (Myxozoa) on gastrointestinal neuromodulators and cell apoptosis of gilthead sea bream (Sparus aurata) - Estensoro, Itziar; Bermúdez, Roberto; Losada, Ana Paula; Quiroga, María Isabel; Pérez-Sánchez, Jaume; Álvarez-Pellitero, Mª del Pilar; Sitjà-Bobadilla, Ariadna (2009)
Trabajo presentado en la 14th EAFP International Conference (European Association of Fish Pathologists), celebrada en Praga (República Checa), del 14 al 19 de septiembre de 2009 Enteromyxum leei affects a broad range of species and is widely spread in the Mediterranean basin, affecting mainly gilthead sea bream and sharpsnout sea bream farms with significant economic losses. The parasite damages the intestinal epithelium producing severe enteritis that impairs absorption of nutrients and osmoregulation [1]. Anorexia, emaciation, cachexy and mortality are the results of the infection. Thus, it is of high interest to study the involvement of different aspects of host-parasite interactions at the gastrointestinal level. The involvement of the digestive neuroendocrine system in the development of the disease has been studied for E. scophthalmi in turbot [2] but no data are available for E. leei. Apoptosis is known to be induced by several parasites. Therefore, the aim of the present work was to evaluate the effects of E. leei on enteroendocrine cells as well as to detect apoptotic cells using tissue samples of control-unexposed (C) and recipient (R) gilthead sea bream experimentally exposed (102 days) to E. leei-contaminated effluent [see 3]. Samples of anterior (Ai), medium (Mi) and posterior (Pi) intestine, head kidney (Hk) and spleen (Spl) were Bouin-fixed and embedded in paraffin. Sections from 5 C and 5 R fish were immunohistochemically probed with heterologous antibodies against the active caspase 3 protease (CAS3), and three neuromodulators: Substance P (SP), Leu-Enkephalin (LEU) and Neuropeptide Y (NPY). Immunoperoxidase-stained cells in 10 digital fields observed at x400 were counted for each fish and tissue and statistical analyses were performed. The number of SP and NPY immunoreactive enteroendocrine cells in R fish was lower than in C fish in the three intestinal segments, though differences were not statistically significant. By contrast, LEU immunoreactive cells were more abundant in R fish, being ...